Common mythos on yield to maturity in bonds or irr in corporate finance - José P. Dapena; Ricardo Schefer (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2020)
The yield to maturity (YTM) or internal rate of return (IRR) is a metric used in financial analysis to estimate the profitability of potential investments. Almost all finance textbooks state the following conditioning assumptions: (i) that the coupon payments can be reinvested at a rate equal to the yield to maturity, (ii) that the bond is held to maturity. We show that there are two common fallacies about these assumptions, and none of them are necessary to interpret this return measure, and they may have probably arisen as a consequence of a semantic misunderstanding. The calculation of the YTM/IRR is the result of an ex ante mathematical operation focusing on current and future cash flows, regardless of the reinvestment rate, which is different from wealth accumulation. At the end of the paper we provide some numerical examples.
Keywords: G31; G12; G11; 330; Yield to maturity; Project evaluation; Internal rate of return; Cash flows